TINJAUAN YURIDIS ALIH FUNGSI MOBIL PRIBADI MENJADI ANGKUTAN UMUM DI KABUPATEN TIMOR TENGAH SELATAN - Balelay, Kirsten R F N; Yohanes, Saryono; Tuba Helan, Yohanes G (Petitum Law Journal, 2024)
Based on Law Number 22 of 2009 concerning Road Traffic and Transportation, transportation operators must have a permit as explained in Article 173, Problem formulation, namely: What are the procedures for using private cars as public transportation in South Central Timor Regency related to the conversion of private car use be public transport. Empirical juridical approach method, the data source is this research is empirical juridical research, namely research based on applicable laws and regulations and data obtained in the field. Based on Law Number 22 of 2009 concerning Road Traffic and Transportation, transportation operators must have a permit as explained in Article 173, the problem statement is: Are there regulations regarding the use of private cars as public transportation in South Central Timor Regency related to conversion of use? Private vehicles are now used for public transit. Empirical juridical approach method, which uses data collected in the field and applicable laws and regulations as its data source, is an empirical approach to research on the law.